ANALISIS PENGARUH KUALITAS LAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA GENERASI Z DALAM INDUSTRI E-COMMERCE - Yusditara, Wisnu (Jurnal KAFEBIS, 2024)
This study analyzes the impact of service quality and promotion on customer satisfaction among Generation Z in the e-commerce industry. The method used is multiple linear regression analysis. The results indicate that both service quality and promotion significantly influence customer satisfaction. Improvements in service quality, such as transaction speed and security, along with engaging promotional strategies, positively contribute to the shopping experience of Generation Z. These findings emphasize the importance of innovation in services and promotions to enhance customer satisfaction and loyalty in the digital era.